THE INFLUENCE OF MARKETING MIX ON PURCHASING DECISIONS AT THE KADOZ WATER DRINKING WATER DEPOT, GUNUNGSITOLI CITY BRANCH - Robil Lase; Idarni Harefa; Maria Magdalena Bate’e; Serniati Zebua (LPPM YPITI, 2026)
This research was conducted at the Kadoz Water drinking water depot, Gunungsitoli City branch. Researchers found that in its marketing activities there are still various shortcomings in each aspect of the marketing mix that have the potential to influence consumer perceptions of the product. The purpose of this study is to determine whether or not there is an influence of the marketing mix on purchasing decisions and how much influence these variables have by using quantitative research methods and distributing questionnaires to 30 consumers of Kadoz Water, Gunungsitoli City branch. The results of this study indicate that there is an influence of the marketing mix (X) on purchasing decisions (Y) as indicated by the results of the t-test, obtained a significance value of 0.005 <0.05, and the calculated t-value (3.054)> t-table (1.701). In the determinant test, it was obtained that the influence of variable X on variable Y was 25% so that in this study that Ha was accepted and Ho was rejected.